2017
DOI: 10.1002/pros.23352
|View full text |Cite
|
Sign up to set email alerts
|

When should active surveillance for prostate cancer stop if no progression is detected?

Abstract: The benefit of AS when compared to CM is strongly dependent on life expectancy and disease risk. Clinicians should take this into account when selecting men to AS, deciding on biopsy frequency and when to stop AS surveillance rounds and transition to CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A recent microsimulation study investigated the optimal age at which AS should be stopped. After such an age, further biopsies would provide no further benefit, indicating that a switch to watchful waiting is warranted ( 31 ). The optimal age at which to stop AS was strongly dependent on the disease risk and life expectancy of a patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent microsimulation study investigated the optimal age at which AS should be stopped. After such an age, further biopsies would provide no further benefit, indicating that a switch to watchful waiting is warranted ( 31 ). The optimal age at which to stop AS was strongly dependent on the disease risk and life expectancy of a patient.…”
Section: Discussionmentioning
confidence: 99%
“…Several simulation studies have been performed aiming to estimate the trade-off between the reduction in number of biopsies taken and the delay in detection of disease reclassification ( 31 - 33 ). Although all studies used different modelling strategies, two studies used data from the Johns Hopkins cohort to calibrate their models ( 33 , 34 ).…”
Section: Protocol Based Monitoring Versus Risk-based Monitoringmentioning
confidence: 99%
“…First, the risk of adverse outcomes because of personalised schedules is quite low because of the low rate of metastases and prostate cancer specific mortality in AS patients (Table 1). Second, studies [8,31] have suggested that after the confirmatory biopsy at 1 year of follow-up, biopsies may be done as infrequently as every 2-3 years, with limited adverse consequences. In other words, longer delays in detecting upgrading may be acceptable after the first negative biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is guidance about when to start AS, discussion or literature on what clinicians consider or have experienced when decreasing the frequency of testing for AS and/or transitioning to WW is largely absent. There is a commentary, 8 few modelling studies 9 10 and a narrative review. 11 These articles indicate that the decision to de-escalate AS and/or convert to WW is complex and needs to consider age, comorbidities and patient preferences.…”
Section: Introductionmentioning
confidence: 99%